Dynamic expression of TET1, TET2, and TET3 dioxygenases in mouse and human placentas throughout gestation. (November 2017) - Rakoczy, Joanna; Padmanabhan, Nisha; Krzak, Ada M.; Kieckbusch, Jens; Cindrova-Davies, Tereza; Watson, Erica D.
Abstract: Introduction: Throughout pregnancy, the placenta dynamically changes as trophoblast progenitors differentiate into mature trophoblast cell subtypes. This process is in part controlled by epigenetic regulation of DNA methylation leading to the inactivation of 'progenitor cell' genes and the activation of 'differentiation' genes. TET methylcytosine dioxygenases convert 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC) during DNA demethylation events. Here, we determine the spatiotemporal expression of TET1, TET2, and TET3 in specific trophoblast cell populations of mouse and human placentas throughout gestation, and consider their role in trophoblast cell differentiation and function. Methods: In situ hybridization analysis was conducted to localize Tet1, Tet2, and Tet3 mRNA at key stages of mouse placental development. The distribution of 5-mC and 5-hmC in these samples was also evaluated. In comparison, expression patterns of TET1, TET2, and TET3 protein in human placentas were determined in first trimester and term pregnancies. Results: In mouse, Tet1-3 mRNA was widely expressed in trophoblast cell populations from embryonic (E) day 8.5 to E12.5 including in progenitor and differentiated cells. However, expression became restricted to specific trophoblast giant cell subtypes by late gestation (E14.5 to E18.5). This coincided with cellular changes in 5-mC and 5-hmC levels. In human, cell columns, extravillous trophoblast and syncytiotrophoblast expressed TET1-3 whereas only TET3 was expressed in villus cytotrophoblast cells in first trimester and term placentas. Discussion: Altogether, our data suggest that TET enzymes may play a dynamic role in the regulation of transcriptional activity of trophoblast progenitors and differentiated cell subtypes in mouse and human placentas. Highlights: TETs are expressed through gestation in human and mouse placentas. Late gestation Tet expression is restricted to specific mouse trophoblast subtypes. Differential TET expression in early and late human placentas was observed. TET expression in trophoblast correlates with 5-hydroxymethylcytosine levels. Trophoblast progenitors and differentiated cells likely require TET function.